2018
DOI: 10.1186/s40066-018-0225-x
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural extension and its effects on farm productivity and income: insight from Northern Ghana

Abstract: Background: In agricultural-dependent economies, extension programmes have been the main conduit for disseminating information on farm technologies, support rural adult learning and assist farmers in developing their farm technical and managerial skills. It is expected that extension programmes will help increase farm productivity, farm revenue, reduce poverty and minimize food insecurity. In this study, we estimate the effects of extension services on farm productivity and income with particular reference to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
93
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(152 citation statements)
references
References 17 publications
16
93
3
Order By: Relevance
“…Contrary to a priori expectation, the frequency of agricultural extension has a significant negative influence on technical efficiency. As emphasized by many previous and recent empirical studies (Evenson 2001, Gautam 2001, Abdulai et al 2017, Danso-Abbeam et al 2018, agricultural extension service is a critical avenue for disseminating information on production technologies, which in turn, spur productivity in smallholder farming system. The negative influence of extension services could be because farmers did not receive the right information at the right time regarding maize production.…”
Section: Determinants Of Technical Efficiencymentioning
confidence: 99%
“…Contrary to a priori expectation, the frequency of agricultural extension has a significant negative influence on technical efficiency. As emphasized by many previous and recent empirical studies (Evenson 2001, Gautam 2001, Abdulai et al 2017, Danso-Abbeam et al 2018, agricultural extension service is a critical avenue for disseminating information on production technologies, which in turn, spur productivity in smallholder farming system. The negative influence of extension services could be because farmers did not receive the right information at the right time regarding maize production.…”
Section: Determinants Of Technical Efficiencymentioning
confidence: 99%
“…Human capital has also been identified as contributing beneficially to several pathways between agricultural productivity and improved nutrition, while also playing significant role in improving agricultural productivity. Enhancing farmers' knowledge and their exposure to technological innovations through training is a key input to improving agricultural productivity (Asfaw and Admassie 2004;Reimers and Klasen 2012;Danso-Abbeam et al 2018;Mariyono 2019;Anang et al 2020). Education may not only influence the decision of farmers to adopt new agricultural technology, but also affect their farming creativeness, innovative ability, and technical efficiency.…”
Section: Linkages Between Agricultural Productivity Change and Nutritmentioning
confidence: 99%
“…In a recent study in Ghana, Anang et al (2020) showed that access to agricultural extension enhanced technology adoption and farm income of peasant farmers. Access to agricultural extension improved technology adoption by farm households (Wossen et al, 2017;Ghimire et al, 2015;Asfaw et al, 2012) as well as household income (Danso-Abbeam et al, 2018;Gebrehiwot, 2015;Davis et al, 2012). Agricultural extension agents train farmers on modern production practices and introduce them to innovative ways of farming to enhance productivity.…”
Section: Introductionmentioning
confidence: 99%